2005
DOI: 10.1073/pnas.0503533102
|View full text |Cite
|
Sign up to set email alerts
|

Experimental tests of a homology model for OxlT, the oxalate transporter of Oxalobacter formigenes

Abstract: Using the x-ray structure of the glycerol 3-phosphate transporter (GlpT), we devised a model for the distantly related oxalate transporter, OxlT. The model accommodates all earlier biochemical information on OxlT, including the idea that Lys-355 lies on the permeation pathway, and predicts that Lys-355 and a second positive center, Arg-272, comprise the binding site for divalent oxalate. Study of R272K, R272A, and R272Q derivatives verifies that Arg-272 is essential, and comparisons with GlpT show that both an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
55
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 29 publications
7
55
0
Order By: Relevance
“…Early work showed that substitution at positions 272 or 355 abolished OxlT function unless the basic character of the original residue was preserved (15)(16)(17). But even like substitutions (e.g., R272K or K355R) yield substantially diminished catalytic activity ( Table 1), suggesting that side-chain architecture in this region is critical.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Early work showed that substitution at positions 272 or 355 abolished OxlT function unless the basic character of the original residue was preserved (15)(16)(17). But even like substitutions (e.g., R272K or K355R) yield substantially diminished catalytic activity ( Table 1), suggesting that side-chain architecture in this region is critical.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of the OxlT homology model (17), as well as earlier biochemical work (11,15,16) suggests that two positively charged residues (R272 and K355) serve as ligand-binding elements for the anionic OxlT substrates. The work reported here supports this hypothesis, in part by showing that a requirement for positive charge at these positions reflects requirements for OxlT function, rather than biogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations